Analysis of Listening Skills in Indonesian Language Learning for 5th Grade Elementary School Using Audio Visual - Efda Zahara; Salsabila Qohsi; Widiya Wahyuni (Journal of Practice Learning and Educational Development, 2026)
Listening ability is one of the important language skills in Indonesian language learning because it serves as the foundation for developing other language skills. This study aims to analyze the listening ability of fifth-grade elementary school students in Indonesian language learning using audio-visual media. The research employed a descriptive qualitative approach. The subjects of this study were 34 fifth-grade students of SDN 111 Pekanbaru selected through purposive sampling technique. Data were collected through observation using a listening ability assessment sheet consisting of five indicators, namely focusing attention, understanding the content of the story, identifying characters and setting, concluding moral messages, and retelling the story. The results showed that 13 students were in the very good category, 19 students in the good category, and 2 students in the fairly good category. Most students were categorized as good, indicating that the use of audio-visual media helped improve students’ attention, comprehension, and ability to retell information they had listened to. Therefore, audio-visual media can be used as an effective learning alternative to improve elementary school students’ listening ability.